Pemaparan Manfaat Pendaftaran Hak Merek Pada UMKM Ngombe Kopi Batam - Winda Fitri; Elvina Enjelica; Felix Filbert; Jeny; Hardy Winata Lie; Jacelyn; Princessa Tan Widiana; Trillian Lim (CV. ULIL ALBAB CORP, 2022)
Intellectual Property Rights (IPR) is defined as the right to obtain legal protection of intellectual property in accordance with the laws and regulations. Legal protection for trademarks is very important so that they are not used by other parties against the law such as plagiarism and counterfeiting which can create unfair trade competition so that it ends up harming the brand owner. Ngombe Kopi Batam SMEs have unique menus that can be used as trademarks. A trademark in MSMEs can also be a way to get closer between MSMEs and customers, with the presence of a brand or trademark, customers will find it easier to remember the MSME trademark. Therefore, it is important for MSMEs to avoid plagiarism in their business by registering their trademarks with Intellectual Property Rights (IPR) of Trademark Rights.